Modified expanded perlite and manufacturing method and application thereof

By modifying the surface of the expanded perlite with silane coupling agent and modifier to form a core-shell structure, the problem of expanding perlite adsorbing too much resin in the resin material is solved, and the effect of reducing the amount of resin and production cost is achieved.

CN119708886APending Publication Date: 2025-03-28JOMOO KITCHEN & BATHROOM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411809304.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When expanding perlite is filled with resin materials, due to its high specific surface area and honeycomb structure, a large amount of resin will be adsorbed, resulting in an increase in the resin ratio and the purpose of reducing costs cannot be achieved.

Method used

The core of expanded perlite is surface modified by the shell composed of silane coupling agent and modifier to form a core-shell structure, reducing the surface energy of expanded perlite, and improving its compatibility and interface binding force.

Benefits of technology

The bulk density of modified expanded perlite is significantly increased, the oil absorption value is reduced, the amount of resin is used, the production cost is reduced, and the uniform dispersion of fillers is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The invention provides modified expanded perlite as well as a preparation method and application thereof. The modified expanded perlite comprises a core-shell structure, the core is expanded perlite, and the shell comprises a silane coupling agent wrapping the expanded perlite and a modifier covering the silane coupling agent. The oil absorption value of the modified expanded perlite is remarkably reduced, so that the modified expanded perlite can be added as a filler in an increased amount, the use amount of resin is remarkably reduced, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of filler materials, and in particular to a modified expanded perlite and a manufacturing method and use thereof. Background Art

[0002] Expanded perlite is a new type of lightweight, multifunctional white granular material with a honeycomb structure inside, which is made by preheating perlite ore in a preheating furnace and then instantaneously calcining and expanding it. It has a hollow honeycomb structure, a high specific surface area, and excellent chemical and thermal stability.

[0003] When perlite is used as a filler in resin materials to achieve the purpose of lightweighting the product, due to its large specific surface area, it has extremely strong adsorption capacity, and its honeycomb structure can form a capillary effect on the liquid. After being added to the resin, it will absorb a large amount of resin. Although the amount of filler is reduced, the resin ratio is increased, and the purpose of cost reduction cannot be achieved.

[0004] Therefore, there is a need for an improved modified expanded perlite and a method for producing and using the same. Summary of the invention

[0005] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.

[0006] In one aspect, the present application provides a modified expanded perlite, comprising a core-shell structure, wherein the core-shell structure comprises a core and a shell, wherein the core is expanded perlite, and the shell comprises a silane coupling agent wrapping the expanded perlite and a modifier covering the silane coupling agent.

[0007] In one embodiment, the silane coupling agent is one of vinyl silane, amino silane and methacryloxy silane.

[0008] In one embodiment, the modifier is an amine-terminated polyol ester.

[0009] In one embodiment, the amine-terminated polyol ester is JL-G02FX.

[0010] In one embodiment, the bulk density of the modified expanded perlite is 0.55 g / cm 3 -0.65 g / cm 3 Optionally, the bulk density of the modified expanded perlite is 0.58 g / cm 3 -0.62 g / cm 3 .

[0011] In another aspect, the present application provides a method for producing the modified expanded perlite, the method comprising the following steps: 100 parts by weight of expanded perlite were crushed to obtain expanded perlite particles with a particle size range of 2-10 μm; Diluting 1-2 parts by weight of a silane coupling agent into a 0.1wt%-0.5wt% aqueous solution of the silane coupling agent, mixing the solution with the expanded pearlite particles, and drying the solution to obtain a first powder sample; The first powder sample is mixed with 1-2 parts by weight of the modifier at a temperature of 90° C. to 110° C. and reacted to obtain the modified expanded perlite.

[0012] In one embodiment, the pulverizing is vibration pulverizing.

[0013] In one embodiment, the drying is spray drying.

[0014] In yet another aspect, the present application provides use of the modified expanded perlite as a filler in reducing the oil absorption value of a resin-containing system.

[0015] In one embodiment, the resin is one of unsaturated polyester, epoxy resin and acrylic resin.

[0016] In yet another aspect, the present application provides use of the modified expanded perlite in manufacturing a thermal insulation material.

[0017] The modified expanded perlite of the present application can be used as a filler and mixed with other materials to manufacture insulation boards, insulation coatings, insulation walls, etc.

[0018] The present application makes the inorganic powder surface organic by bonding silane coupling agent molecules on the surface of expanded perlite particles, and mutually associating and aggregating to form a network structure film covering the surface of the powder particles. Therefore, even if the filling amount is increased and the resin amount is reduced, it can still be well dispersed; at the same time, multiple functional groups in the terminal amine polyol ester modifier are used, such as some inorganic-philic ends (such as amine groups, etc.) are adsorbed on the surface of perlite, and chemically react with active sites such as hydroxyl groups and oxygen bridges to form strong chemical bonds; hydroxyl groups in the terminal amine polyol ester undergo condensation reactions with groups such as silane groups in the silane coupling agent to form chemical bonds such as silicon-oxygen bonds; amine groups in the terminal amine polyol ester undergo addition reactions with unsaturated bonds (such as carbon-carbon double bonds) in the silane coupling agent to form new chemical bonds, etc.; through the multi-point adsorption of these "anchor" groups, the compatibility and interfacial bonding force of the expanded perlite and the organic polymer are further improved.

[0019] The present application uses a shell composed of a silane coupling agent and a modifier to modify the surface of the expanded perlite core to achieve surface chemical reactive coating, thereby effectively reducing the surface energy of the expanded perlite as a filler, weakening its surface polarity, reducing the friction between particles, improving lubricity, and stacking more densely, thereby significantly increasing the stacking density and reducing the oil absorption value.

[0020] The modified expanded perlite prepared in the present application can be added as a filler in an increased amount into a resin-containing system, thereby significantly reducing the amount of resin used and lowering production costs.

[0021] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0023] Figure 1 A scanning electron microscope photograph of the modified expanded perlite prepared in Example 3 of the present application; and Figure 2 This is a scanning electron microscope photograph of the expanded perlite of Comparative Example 4 of the present application. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application are described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0025] Unless otherwise specified, the materials used in the following examples and comparative examples are commercially available.

[0026] The bulk density in the following examples and comparative examples can be measured by a pressure method or other common methods.

[0027] Example 1 100 parts by weight of expanded perlite (industrial grade, purchased from Shijiazhuang Hualang Mining Trading Co., Ltd., 50 mesh) was vibrated and crushed to obtain expanded perlite particles with a particle size range of 2-10 μm; 1 part by weight of an aminosilane coupling agent (purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-550) was diluted to a 0.1 wt % aqueous solution of the aminosilane coupling agent, and then mixed with expanded perlite particles, and spray-dried to obtain a first powder sample; At a temperature of 90° C., the first powder sample was mixed with 1 part by weight of a modifier (purchased from Nanjing Jinlaiwang New Material Technology Co., Ltd., model JL-G02FX) in a high-speed mixer and reacted for 10 minutes to obtain modified expanded perlite.

[0028] The bulk density of the modified expanded perlite prepared in this example is about 0.58 g / cm 3 .

[0029] Example 2 100 parts by weight of expanded perlite (industrial grade, purchased from Shijiazhuang Hualang Mining Trading Co., Ltd., 50 mesh) was vibrated and crushed to obtain expanded perlite particles with a particle size range of 2-10 μm; 2 parts by weight of an aminosilane coupling agent (purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-550) was diluted to a 0.2 wt % aqueous solution of the aminosilane coupling agent, and then mixed with expanded perlite particles, and spray-dried to obtain a first powder sample; At a temperature of 100° C., the first powder sample was mixed with 1.5 parts by weight of a modifier (purchased from Nanjing Jinlaiwang New Material Technology Co., Ltd., model JL-G02FX) in a high-speed mixer and reacted for 10 minutes to obtain modified expanded perlite.

[0030] The bulk density of the modified expanded perlite prepared in this example is about 0.61 g / cm 3 .

[0031] Example 3 100 parts by weight of expanded perlite (industrial grade, purchased from Shijiazhuang Hualang Mining Trading Co., Ltd., 50 mesh) was vibrated and crushed to obtain expanded perlite particles with a particle size range of 2-10 μm; 1 part by weight of an aminosilane coupling agent (purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-550) was diluted to a 0.2 wt % aqueous solution of the aminosilane coupling agent, and then mixed with expanded perlite particles, and spray-dried to obtain a first powder sample; At a temperature of 100° C., the first powder sample was mixed with 2 parts by weight of a modifier (purchased from Nanjing Jinlaiwang New Material Technology Co., Ltd., model JL-G02FX) in a high-speed mixer and reacted for 10 minutes to obtain modified expanded perlite.

[0032] The bulk density of the modified expanded perlite prepared in this example is about 0.62 g / cm 3 .

[0033] Figure 1 : is a scanning electron microscope photo of the modified expanded perlite obtained in this example. Figure 1 It can be seen that the modified expanded perlite has changed from a porous structure before modification to particles with a nearly flaky structure.

[0034] Comparative Example 1 100 parts by weight of expanded perlite particles (industrial grade, purchased from Shijiazhuang Hualang Mining Trading Co., Ltd., 50 mesh) were vibrated and crushed to obtain expanded perlite particles with a particle size range of 2-10 μm.

[0035] Comparative Example 2 100 parts by weight of expanded perlite particles (industrial grade, purchased from Shijiazhuang Hualang Mining Trading Co., Ltd., 50 mesh) were vibrated and crushed to obtain expanded perlite particles with a particle size of 2-10 μm; 0.5 parts by weight of aminosilane coupling agent (purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-550) was diluted to a 0.05 wt% aqueous solution of aminosilane coupling agent, and then mixed with expanded perlite particles, and spray-dried to obtain expanded perlite coated with silane coupling agent.

[0036] Comparative Example 3 100 parts by weight of expanded perlite particles (industrial grade, purchased from Shijiazhuang Hualang Mining Trading Co., Ltd., 50 mesh) were vibrated and crushed to obtain expanded perlite particles with a particle size range of 2-10 μm; 1 part by weight of aminosilane coupling agent (purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-550) was diluted to a 0.1 wt% aqueous solution of aminosilane coupling agent, and then mixed with expanded perlite particles, and spray-dried to obtain expanded perlite coated with silane coupling agent.

[0037] Comparative Example 4 Commercially available unmodified expanded perlite was used. Figure 2 This is a scanning electron microscope photo of the expanded perlite of this comparative example. Figure 2 As shown, the unmodified expanded perlite available on the market has a porous structure and is in the form of approximately spherical particles.

[0038] In addition, the bulk density of the expanded perlite of Comparative Example 3 and Comparative Example 4 was measured, which were about 0.53 g / cm 3 and about 0.076 g / cm 3 .

[0039] Oil absorption measurement The oil absorption value of expanded perlite is also called the resin adsorption amount, which is an index of the resin absorption amount of the expanded perlite as a filler.

[0040] The oil absorption value of the modified expanded perlite of the present application is measured based on weight. The measurement process may include the following steps:

[0041] Accurately weigh the expanded perlite to be tested, wrap it with gauze and put it into a beaker, and weigh the total weight; Add a certain amount of resin liquid into the beaker to fully soak the expanded perlite and ensure that the resin liquid to be tested fully contacts the surface of the expanded perlite; After a certain period of liquid absorption, the soaked expanded perlite is taken out, the gauze is untied, and the gauze is returned to the beaker; Weigh the beaker and gauze again, calculate the difference in the mass of the adsorbed liquid, and you can get the oil absorption of the expanded perlite. Calculate the oil absorption value as weight percent: Oil absorption value (weight %) = (resin used (g) / weight of expanded perlite (g)) x 100.

[0042] The oil absorption value can be measured by using one of unsaturated polyester, epoxy resin and acrylic resin. The present application uses unsaturated polyester purchased from Xinyang Technology Group Co., Ltd., model DC191.

[0043] The oil absorption values ​​of the modified expanded perlite obtained in each example and the expanded perlite obtained in each comparative example were measured, and the results are shown in Table 1 below.

[0044] Table 1 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Oil absorption value 82.3% 73.5% 68.5% 166.2% 133.6% 118.2% 213.1% From the results in Table 1, it can be seen that the modified expanded perlite prepared in the embodiment of the present application is added as a filler to a resin system, such as an unsaturated polyester resin system, which significantly reduces the oil absorption value of the modified expanded perlite. The modified expanded perlite with a low oil absorption value can be used as a filler to increase the filling amount, and accordingly, the amount of resin used can be significantly reduced, thereby reducing costs.

[0045] based on Figure 1 , Figure 2As shown in Table 1, it can be considered that due to the porous structure of the unmodified expanded perlite, the resin adsorption occurs not only on the surface, but also penetrates into the internal pores to form multi-layer adsorption, and the adsorption amount is relatively high; and due to the characteristics of the modified expanded perlite prepared in the present application, the resin adsorption mainly occurs on the surface, and the adsorption sites are limited, thereby significantly reducing the adsorption amount; compared with the porous structure of the unmodified expanded perlite, the modified expanded perlite prepared in the present application has a more regular and compact approximate lamellar structure, which reduces the voids and gaps between the particles, and the close arrangement reduces the air volume between the particles, thereby increasing the packing density; during the modification process, most of the pores of the expanded perlite are destroyed or blocked, resulting in a decrease in the number of pores, thereby reducing the air content inside the particles, thereby increasing the packing density, and reducing and closing the pores no longer contribute to the adsorption of the resin, thereby also resulting in a decrease in the resin adsorption amount. In addition, the modification method of the present application can further effectively reduce the surface energy of the modified expanded perlite used as a filler, thereby weakening its surface polarity, reducing the friction between particles, improving lubricity, enabling it to be stacked more densely, further increasing its stacking density, and further reducing its oil absorption value.

[0046] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A modified expanded perlite, characterized in that: The invention comprises a core-shell structure, wherein the core-shell structure comprises a core and a shell, wherein the core is expanded perlite, and the shell comprises a silane coupling agent wrapping the expanded perlite and a modifier covering the silane coupling agent.

2. The modified expanded perlite according to claim 1, characterized in that: The silane coupling agent is one of vinyl silane, amino silane and methacryloxy silane.

3. The modified expanded perlite according to claim 1, characterized in that: The modifier is an amine-terminated polyol ester.

4. The modified expanded perlite according to claim 3, characterized in that: The amine-terminated polyol ester is JL-G02FX.

5. The modified expanded perlite according to any one of claims 1 to 4, characterized in that: The bulk density of the modified expanded perlite is 0.55 g / cm 3 -0.65 g / cm 3 .

6. A method for producing the modified expanded perlite according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: 100 parts by weight of expanded perlite were crushed to obtain expanded perlite particles with a particle size range of 2-10 μm; Diluting 1-2 parts by weight of a silane coupling agent into a 0.1wt%-0.5wt% aqueous solution of the silane coupling agent, mixing the solution with the expanded pearlite particles, and drying the solution to obtain a first powder sample; The first powder sample is mixed with 1-2 parts by weight of the modifier at a temperature of 90° C. to 110° C. and reacted to obtain the modified expanded perlite.

7. The method for producing modified expanded perlite according to claim 6, characterized in that: The pulverization is vibration pulverization; and / or, The drying is spray drying.

8. Use of the modified expanded perlite according to any one of claims 1 to 5 as a filler in reducing the oil absorption value of a resin-containing system.

9. The use according to claim 8, characterized in that The resin is one of unsaturated polyester, epoxy resin and acrylic resin.

10. Use of the modified expanded perlite according to any one of claims 1 to 5 in the manufacture of thermal insulation materials.

Citation Information

Cited By

  • Aerated concrete floor support plate as well as preparation method and application thereof

    CN122145093A